OnabotulinumtoxinA treatment of moderate to severe glabellar lines in Chinese subjects after laser therapy: A prospective, open-label, noncomparative study. (4th July 2018) - Wu, Yan; Lu, Zhong; Xie, Yong; Zhang, Wei; Chen, Xiangdong; Shi, Yuling; Li, Qin; Halstead, Michael; Rogers, John D; Silberberg, Michael
ABSTRACT: Introduction : This study evaluated safety and efficacy of onabotulinumtoxinA for moderate to severe glabellar lines (GL) following laser therapy in Chinese subjects. Materials and Methods : Subjects ( n  = 173) were followed for 120 days following a single onabotulinumtoxinA (20 U) treatment for GL after recent laser therapy. Subjects completed validated patient-reported outcomes, including Facial Lines Outcome 11-item (FLO-11) Questionnaire and Facial Lines Satisfaction Questionnaire (FLSQ). Physicians and subjects assessed GL severity at maximum frown and at rest using the Facial Wrinkle Scale with Asian Photonumeric Guide (FWS-A). Results : Mean total FLO-11 scores increased from 47.7 (baseline) to 75.9 (day 120) ( p  < 0.0001), with mean improvement of at least two grades for most items maintained to day 120. Most subjects were mostly or very satisfied, per the FLSQ. Percentages of subjects with at least one-grade improvement in FWS-A (responders) at maximum frown per subjects and physicians were 93.1% and 97.1%, respectively, at day 30, and 72.3% and 81.5% at day 120 (all, p  < 0.0001). More than 70% were FWS-A responders at day 120. All adverse events were mild or moderate; none were related to onabotulinumtoxinA. Conclusions : A single onabotulinumtoxinA (20 U) treatment following laser therapy was safe and effective in correcting GL for up to 120 days.